The Effectiveness of Limbal Stem Cell Transplantation on Ocular Surface Restoration and Corneal Clarity : A Systematic Review - Faidil Akbar (The International Journal of Medical Science and Health Research, 2026)
Introduction: Limbal stem cell deficiency (LSCD) leads to corneal conjunctivalization, neovascularization, and vision loss. This systematic review evaluates the effectiveness of various limbal stem cell transplantation (LSCT) techniques on ocular surface restoration and corneal clarity. Methods: A systematic review of human studies (RCTs, etc) reporting quantitative outcomes of LSCT for LSCD or severe ocular surface disorders was performed. Studies had a minimum 3-month follow-up. Outcomes extracted included anatomical success, visual acuity changes, corneal clarity, neovascularization regression, and safety profiles. Results: Across 24 included studies, LSCT consistently achieved anatomical surface restoration in 67-92% of eyes. Techniques such as SLET, CLET, CLAU, and MSCT showed equivalent surface stabilization. However, visual acuity gains were often modest in bilateral or severe LSCD due to underlying stromal scarring (Zakaria et al., 2014; Calonge et al., 2019). Corneal clarity improved significantly with SLET, MSCT, and COMET, but not with CLET alone (Sharma et al., 2024; Calonge et al., 2019; Tandon et al., 2024). Neovascularization consistently regressed across all techniques (Arora et al., 2017; Jurkunas et al., 2025). In pterygium, LSCT reduced recurrence rates to 0-12.5% compared to 17.5-30.4% with excision alone (Mu et al., 2012; Yu, 2026). Safety was favorable, with no serious cell-related adverse events. Discussion: A key dissociation exists between successful surface restoration and visual recovery, as LSCT addresses epithelial but not stromal pathology. Etiology is a major moderator: chemical burns respond best, while autoimmune diseases have poorer outcomes. Adjunctive amniotic membrane sustains long-term effects only when combined with stem cells. Manufacturing quality and cell confluence predict success. Conclusion: LSCT is effective for ocular surface restoration and neovascularization reduction. However, visual recovery requires sequential keratoplasty for stromal opacity. Technique selection should be etiology-driven, and standardized manufacturing protocols are recommended for future trials.